Snake beans (Vigna sinensis (L) Savi ex Hassk) extract increases breast epithelial cells proliferation - Edy Meiyanto; Sri Handayani; Riris Istighfari Jenie (Indonesian Journal of Pharmacy, 2008)
Some Javaness people use snake beans for skin and breast care, especially for better breast development. This research was conducted to examine the effect of snake beans extract (EKP) on the breast epithelial cells proliferation on in vitro and in vivo models. The in vitro experiment was carried out against MCF-7 cells using MTT assay and morphologically examination was carried out under light microscope. Sprague Dawley female Rats were used in in vivo experiment. The rats (30 days of age) were separated into 3 groups, namely base line group, control group, and treatment groups. The extract was administered in the dose of 1000 mg/kgBW p.o. every day for 14 days then the rats were examined for wet uterus weight, lobulus development, and estrogen receptor (ER) expression. Extract treatment induced MCF-7 cells proliferation in dose dependent manner. The extract exhibited proliferative effect in the dose of 50 ug/mL 300 ug/mL, but in the dose of 400 ug/mL and 500 ug/mL the extract inhibited cells proliferation and there were no cell death effect. Extract treatment in the dose of 1000 mg/kgBW tended to increase uterus weight. The extract also increased lobulus development up to two fold and induced estrogen receptor expression in epithelial cells of lobulus and ductus. These results conclude, snake bean (in appropriate dose) induces breast glands development and relatively safe (no death effect on the cells), therefore can be developed for breast care product.Key words: Snake bean, breast care, proliferation, lobulus epithelial cells, estrogen receptor